Layanan Mandiri di Perpustakaan SMA Negeri 5 Magelang: Menjawab Tantangan Generasi Milenial - Suryanto Suryanto (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
School library is a library located in a school that shelters it. The library has the main objective, namely to support teaching and learning activities. In the current era, pemustaka in senior high schools (SMA) are users who are classified as the millennial generation. Millennial generation has characteristic of making technology a lifestile. Millennials want speed in their every life. The speed at which they wanted made them prefer something simple. Millennials are also more comfortable using technology so that they can do things independently and in a structured manner. Libraries need to innovate in providing services to visitors to match the characteristics of the millennial generation. SMA Negeri 5 Magelang Library implements independent services in responding to the challenges of the millennial generation. The implementation of self-service in the SMA Negeri 5 Magelang Library can be said to be easy and simple. However, there is a need for hardware upgrades so that self-service can run better. It should also be noted regarding security and librarians must be diligent in doing database backups so that at any time when a problem occurs, the data is well preserved.